Future strategy for Musa improvement - Ortíz, R.; Vuylsteke, D.R. (1994)
IITA has increased its knowledge about major constraints across agro-ecological zones and gene pools for Musa production in Africa. The authors review the following different aspects: adding more desirable attributes to breeding populations; integration of host-plant resistance, enhanced utilization, and improved cropping systems; networking; and training.